The Conversion of a Cork Candle-MakerAn Account by Hester Ann Rogers (1788) - Holloway, Luke (Wesley and Methodist studies, 2022)
In 1788, Cork candle-maker Cadwallader Acteson was driven to repent of his sins by a host of otherworldly visitants. The story was recorded and circulated in manuscript, almost certainly by the Methodist writer Hester Ann Rogers. This article is a transcription of the copy, ascribed to Elizabeth Ritchie, that resides at the Methodist Archives and Research Centre, John Rylands Research Institute and Library, Manchester. Cadwallader's idiosyncratic story offers a window into gender roles and conceptions of agency in the late eighteenth century, and sheds light on how Methodist notions of the conversion experience might fuse with the beliefs of local communities.